Adventures and Advances in Time Travel With Induced Pluripotent Stem Cells and Automated Patch Clamp - Rosholm, Kadla R.; Badone, Beatrice; Karatsiompani, Stefania; Nagy, David; Seibertz, Fitzwilliam; Voigt, Niels; Bell, Damian C. (Frontiers in Molecular Neuroscience, 2022)
In the Hollywood blockbuster ‘The Curious Case of Benjamin Button’, a fantastical fable unfolds of a man’s life that travels through time reversing the aging process; as the tale progresses, the frail old man becomes a vigorous, vivacious young man, then man becomes boy and boy becomes baby. The reality of cellular time travel, however, is far more wondrous: we now have the ability to both reverse and then forward time on mature cells. Four proteins were found to rewind the molecular clock of adult cells back to their embryonic, ‘blank canvas’ pluripotent stem cell state, allowing these pluripotent stem cells to then be differentiated to fast forward their molecular clocks to the desired adult specialist cell types. These four proteins - the ‘Yamanaka factors’ - form critical elements of this cellular time travel, which deservedly won Shinya Yamanaka the Nobel Prize for his lab’s work discovering them. Human induced pluripotent stem cells (hiPSCs) hold much promise in our understanding of physiology and medicine. They encapsulate the signaling pathways of the desired cell types, such as cardiomyocytes or neurons, and thus act as model cells for defining the critical ion channel activity in healthy and disease states. Since hiPSCs can be derived from any patient, highly specific, personalized (or stratified) physiology and/or pathophysiology can be defined, leading to exciting developments in personalized medicines and interventions. As such, hiPSC married with high throughput automated patch clamp (APC) ion channel recording platforms provide a foundation for significant physiological, medical and drug discovery advances. This review aims to summarize the current state of affairs of hiPSC and APC: the background and recent advances made; and the pros, cons and challenges of these technologies. Whilst the authors have yet to finalize a fully functional time travelling machine, they will endeavor to provide plausible future projections on where hiPSC and APC are likely to carry us. One future projection the authors are confident in making is the increasing necessity and adoption of these technologies in the discovery of the next blockbuster, this time a life-enhancing ion channel drug, not a fantastical movie.